KAJIAN SEDIMENTASI RENCANA BANGUNAN PENAHAN SEDIMEN SUNGAI KAPUR KECIL - Siswanto -; Manyuk Fauzi; Hendra Muchlis (Jurnal APTEK, 2013)
Reduction of forests due to human needs has a negative impact on a watershed, one of the effects of the reduction of the forest is the occurrence of erosion and sedimentation on Kapur Kecil river . To determine the sedimentation rate used method of USLE (Universal Soil Loss Equation). USLE method considering the land use on study area, thus this method can be relied upon as an analysis of the amount of sedimentation. The results showed that the sedimentation that occurs based on USLE method of 0,13 mm/year and sedimentation volume of 8,517.65 m3/year.